Selebtwits: Micro-Celebrity Practitioners in Indonesian Twittersphere - Rahmawan, Detta (Jurnal Kajian Komunikasi, 2014)
Drawn from the notion that Twitter is a suitable context for micro-celebrity practices (Marwick, 2010) this research examines interactions between Indonesian Twitter-celebrities called selebtwits and their followers. The results suggest that several strategies include: stimulated conversation, audience recognition, and various level of self-disclosure that have been conducted by the selebtwits to maintain the relationship with their followers. This research also found that from the follower viewpoint, interaction with selebtwits is often perceived as an âendorsementâ and âachievementâ. However, there are others who are not particularly fond of the idea of the selebtwits-followerâs engagement. Some selebtwits-followersâ interactions lead to âdigital intimacyâ, while others resemble parasocial interaction and one-way communication. Furthermore, this study suggests that in the broader context, selebtwits are perceived in both positive and negative ways.Â Â